Upaya Peningkatan Bersihan Jalan Napas Pada Anak Dengan Ispa - Nunung Sukmawati, Meika, Irdawati S. Kep., Ns, Msi. Med (2017)
ISPA is acute of infection involved upper and under part duct breathing organ. This infection cause of fungus virus and bacteria. ISPA have a minor impotance of indication usual beginning by fever, cough, nasal congestion and painful thoart. Infant and childern can't regulate clean pure path in order to satisfy, so they are ISPA immediatially for them which can not handled uneffective cleaning pure path. Infant and childern having uneffective cleaning pure payh of highest risk to shortness of breath and death .The method can be used to treat airway clearance in accordance with the nursing care in patiemts with impaired airway hygine. One of the nursing action that can be done independently is with steam inhalation, chest physiotherapy ang effective cough. After conducting independent action vapor inhalation, chest physiotherapy and effective cough sputum can exit it can be concluded that airway clearance can be resolved. Continued intervention by the patient's mother independently at home to provide steam inhalation, chest physiotherapy and effectively if his cough reccured. Keywords : ISPA , nursing care, vapor inhalation, chest physiotheraphy and effective cough.